Study of the possibility of controlling the production of low-molecular-weight heparin preparations by domestic test systems (review) - A. L. Berkovsky; E. V. Sergeeva; A. V. Suvorov (Разработка и регистрация лекарственных средств, 2024)
Introduction. The data on the wide clinical use of low-molecular-weight heparin (LMWH) preparations are presented, necessitating the need for efficient and high-quality production of appropriate pharmaceuticals. The revealed variability of anticoagulant activity of LMWH preparations implies the provision of production with validated methods of control and certification. The aim of the work is to study the possibility of control of anticoagulant activity and assessment of functional compatibility of LMWH preparations when using domestic test systems.Text. The data on analytical characteristics of chromogenic and coagulometric methods performed with the help of domestic test systems are presented. Their parameters correspond with the existing international requirements. The possibility of the mentioned methods to certify LMWH preparations correctly and reproducibly is shown. The given research results testify to the possibility of clotting methods to determine the bioequivalence of the studied preparations of LMWH.Conclusion. The presented data prove the expediency of production control and certification of LMWH preparations by domestic test systems.